2019
DOI: 10.14710/ijoce.v1i1.6262
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Digital Citra Satelit Worldview-2 untuk Ekstraksi Kedalaman Perairan Laut di Sebagian Perairan Pulau Parang, Kepulauan Karimunjawa, Provinsi Jawa Tengah

Abstract: Teknologi penginderaan jauh (remote sensing) memungkinkan untuk dilakukannya pemetaan batimetri perairan pada daerah yang memiliki tingkat perubahan kedalaman secara cepat dan juga dangkal sekalipun dengan menggunakan citra satelit. Tujuan dari penelitian ini yaitu untuk mengetetahui pasangan band rasio terbaik dari citra satelit Worldview-2  untuk membuat peta batimetri pada perairan serta mengetahui informasi kedalaman di Pulau Parang, Kepulauan Karimunjawa. Penelitian ini menggunakan citra satelit Worldview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
1
0
Order By: Relevance
“…These results align with the research of [19] who reported that the correlation coefficient value of the blue band ratio with the green band is much higher than the ratio of other band combinations. Other researchs conducted by [20,21,22,23] also reported that the combination of blue band and green band in Sentinel-2A image has excellent penetration among other band combinations in mapping bathymetry. The wavelength affects the strength of light penetration in the waters, the shorter the wavelength used, the stronger the ability to penetrate the water column.…”
Section: Bathymetry Algorithmsmentioning
confidence: 91%
“…These results align with the research of [19] who reported that the correlation coefficient value of the blue band ratio with the green band is much higher than the ratio of other band combinations. Other researchs conducted by [20,21,22,23] also reported that the combination of blue band and green band in Sentinel-2A image has excellent penetration among other band combinations in mapping bathymetry. The wavelength affects the strength of light penetration in the waters, the shorter the wavelength used, the stronger the ability to penetrate the water column.…”
Section: Bathymetry Algorithmsmentioning
confidence: 91%
“…MAE is the calculation of the average absolute error between the difference in the actual depth value of field measurements and the predicted depth value of Satellite Derived Bathymetry image processing. The following equations ( 4) and ( 5) are the equations used in the accuracy test [22].…”
Section: Shallow Water Depth Mapping With the Lyzenga Methodsmentioning
confidence: 99%
“…In-situ Depth Sample Distribution 2.1.6. Shallow Water Depth Mapping with the Lyzenga MethodThe Lyzenga algorithm was applied to empirical SDB in this investigation[22]. The premise behind the method developed by David R. Lyzenga in 1985 is that different wavelengths (bands) have different water attenuation coefficients.…”
mentioning
confidence: 99%
“…Perairan Pulau Genting memiliki keanekaragaman sumber daya alam yang tinggi dan bernilai ekonomis bagi warga sekitar (Chikmawati, 2019). Pemetaan kedalaman perairan di Kepulauan Karimunjawa dengan memanfaatkan data citra satelit telah dilakukan sebelumnya antara lain oleh Irwanto, 2018;Syaiful et al, 2019;Aldin et al, 2020;Anida et al, 2020;Prayoga dan Basith, 2020;Mahestro, 2023. Gambar 1. Lokasi Penelitian dan Jalur pemeruman Rencana Data yang digunakan pada penelitian terdiri dari data primer dan data sekunder.…”
Section: Materi Dan Metodeunclassified